Exploring services science : 7th International Conference, IESS 2016, Bucharest, Romania, May 25-27, 2016. Proceedings /: 7th International Conference, IESS 2016, Bucharest, Romania, May 25-27, 2016. Proceedings. (2016) - Unknown
No abstract available